Model Pembacaan Basmalah pada Surah al-Fâtih?ah dalam Shalat; Kajian Hadis Tah?lîlîy - Rustina N (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2018)
This hadith through two chain lines; Anas and Mughaffal. For the history of Anas, there is no diversity in his lafadz, except in muwaththa’ having the difference of lafadz because of the other likelihood and the possibility of tanawwu’ in this hadith. While the history of Mughaffal is the diversity of lafadz. This history of Muslim is of shahih and muttashil. There are three versions of basmalah reading model on jahriyah prayer; Shafi’iyyah argues basmalah sunnah read aloud (jahr). With the basis of the argument stating basmalah is the part of al-fatihah that must be read jahr; Some scholars believe basmalah sunnah is read softly (sirr). This is the opinion of al-Bukhari, Muslim, al-Zaila’i, Ibnul Qayyim, Hanafiyyah, and Hanabilah with the basis of absence of the shahih and sharih that the Prophet hardened basmalah reading; and Malikiyyah argues that reading is jahr. Ibn Taymiyah explains that none of the hadith expressly basmalah reading jahr, but there is a history that the Prophet had hardened basmalah readings, so the right is the Prophet sometimes basmalah and sometimes breaks it, but most often it is toss it down so that’s more important. Basmalah is read by jahr because of the existence of a great ally to achieve.